An Injection from the Tip of your Pen: The Formation of Modern Romani Writing on the Pages of Románo ľil Magazine and its Predecessor Informační zpravodaj 1969–1973 - Ryvolová, Karolína (Romano džaniben, 2019)
This paper fills out some of the blanks in our knowledge about the earliest specimens of Romani press in the Czech Republic, Informační zpravodaj and Románo ľil. It traces the history of struggle of Romani elites to establish their own ethnic magazine from 1957 to 1990. As the said magazines also became the very first platform of consistent Romani literary works’ publication, this study offers a comprehensive description of their so-far little known literary content along with the basic analysis thereof, revealing some interesting new personalities which have as yet escaped the attention of relevant scholars.